Sacral neuromodulation remote programming in patients with refractory lower urinary tract dysfunction: China’s experience during the COVID-19 pandemic - Meng, Lingfeng; Hou, Huimin; Zhang, Peng; Gu, Yinjun; Shi, Benkang; Li, Yan; Wang, Qingwei; Zhang, Yifei; Ren, Lijuan; Chen, Qi; Yuan, Zhen; Guo, Fan; et al. (Frontiers in Medicine, 2023)
Objectives Sacral neuromodulation is an effective, minimally invasive treatment for refractory lower urinary tract dysfunction. However, regular postoperative programming is crucial for the maintenance of the curative effects of electronic sacral stimulator devices. The outbreak of coronavirus disease 2019 (COVID-19) limited the ability of practitioners to perform traditional face-to-face programming of these stimulators. Therefore, this study aimed to evaluate the application of remote programming technology for sacral neuromodulation during the COVID-19 pandemic in China. Materials and methods We retrospectively collected data including baseline and programming information of all patients with lower urinary tract dysfunction who underwent sacral neuromodulation remote programming in China after the outbreak of COVID-19 (i.e., December 2019). The patients also completed a self-designed telephone questionnaire on the subject. Results A total of 51 patients from 16 centers were included. They underwent 180 total remote programming visits, and 118, 2, 25, and 54 voltage, current, pulse width, and frequency adjustments, respectively, were performed. Additionally, remote switching on and off was performed 8 times; impedance test, 54 times; and stimulation contact replacement, 25 times. The demand for remote programming was the highest during the first 6 months of sacral neuromodulation (average, 2.39 times per person). In total, 36 out of the 51 patients completed the questionnaire survey. Of these, all indicated that they chose remote programming to minimize unnecessary travel because they had been affected by COVID-19. The questionnaire also showed that remote programming could reduce the number of patient visits to the hospital, save time, reduce financial costs, and would be easy for patients to master. All surveyed patients indicated that they were satisfied with remote programming and were willing to recommend it to other patients. Conclusion Remote programming for sacral neuromodulation is feasible, effective, safe, and highly recommended by patients with refractory lower urinary tract dysfunction. Remote programming technology has great development and application potential in the post-pandemic era.